2022
DOI: 10.21037/atm-22-259
|View full text |Cite
|
Sign up to set email alerts
|

A narrative review of research advances in hypoxic pulmonary hypertension

Abstract: Background and Objective: Hypoxic pulmonary hypertension (HPH) is a pathological syndrome characterized by pulmonary vasoconstriction and pulmonary vascular remodeling caused by hypoxia, which eventually leads to right heart failure or death. There are 2 stages of onset of HPH: hypoxic pulmonary vasoconstriction (HPV) and hypoxic pulmonary vascular remodeling (HPVR). It is an important pathophysiological link in the pathogenesis of chronic obstructive pulmonary disease (COPD) and chronic mountain sickness (CMS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 83 publications
0
3
0
Order By: Relevance
“…After the formation of PAH, as symptoms such as thickening of the pulmonary vascular wall, narrowing of the lumen, and right ventricular compensation worsen, chronic hypoxia induces oxidative stress and in ammatory responses. In ammation and oxidative stress further damage pulmonary vascular endothelial function, causing an imbalance in the expression of vasoconstrictors and further vasoconstriction, forming a vicious cycle [23,24]. Our study examined the effects of SAL on oxidative stress and in ammatory mediators in the lung tissue of PAH model rats.…”
Section: Discussionmentioning
confidence: 99%
“…After the formation of PAH, as symptoms such as thickening of the pulmonary vascular wall, narrowing of the lumen, and right ventricular compensation worsen, chronic hypoxia induces oxidative stress and in ammatory responses. In ammation and oxidative stress further damage pulmonary vascular endothelial function, causing an imbalance in the expression of vasoconstrictors and further vasoconstriction, forming a vicious cycle [23,24]. Our study examined the effects of SAL on oxidative stress and in ammatory mediators in the lung tissue of PAH model rats.…”
Section: Discussionmentioning
confidence: 99%
“…Oxygen therapy is also recommended for high-altitude PH, although the ideal course of action is relocation to low-altitude areas [ 32 ].…”
Section: Treatmentmentioning
confidence: 99%
“…In recent years, hypoxic pulmonary hypertension has become a research hotspot. The pathological process of PAH includes pulmonary vascular contraction and pulmonary vascular remodeling, and hypoxia is an important inducing factor in pulmonary vascular remodeling [ 2 ]. A previous study has shown that oxidative stress (OS) is a critical mechanism in the pathogenesis of PAH.…”
Section: Introductionmentioning
confidence: 99%